2002
DOI: 10.1614/0043-1745(2002)050[0773:cpfwct]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Critical period for weed control: the concept and data analysis

Abstract: The critical period for weed control (CPWC) is a period in the crop growth cycle during which weeds must be controlled to prevent yield losses. Knowing the CPWC is useful in making decisions on the need for and timing of weed control and in achieving efficient herbicide use from both biological and economic perspectives. An increase in the use of herbicide-tolerant crops, especially soybean resistant to gly-phosate, has stimulated interest in the concept of CPWC. Recently, several studies examined this concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
513
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(527 citation statements)
references
References 34 publications
5
513
0
9
Order By: Relevance
“…The extent of interference periods depends on the competition between the crop and the weeds due to the specific differences among species in morphology, physiology and development. From this evaluation, the CPIP may be unique to each crop and it varies according to the composition and density of the weed population, as well as the time of onset compared to the crop (Knezevic et al, 2002). The cropping system and management practices also influence the extent of the interference periods (Carvalho et al, 2008b;, as well as edaphic climatic factors.…”
Section: Phytosociological Survey and Weed Interference In Eggplants mentioning
confidence: 99%
“…The extent of interference periods depends on the competition between the crop and the weeds due to the specific differences among species in morphology, physiology and development. From this evaluation, the CPIP may be unique to each crop and it varies according to the composition and density of the weed population, as well as the time of onset compared to the crop (Knezevic et al, 2002). The cropping system and management practices also influence the extent of the interference periods (Carvalho et al, 2008b;, as well as edaphic climatic factors.…”
Section: Phytosociological Survey and Weed Interference In Eggplants mentioning
confidence: 99%
“…Early plant vigour is particularly important in annual crop production. Extensive research has identified the stage(s) in which crops are most susceptible to weed competition, the so-called critical weed-free period, and this is often during the crop establishment and early growth stages (Knezevic et al 2002;Seem et al 2003). …”
Section: Increasing Crop Competitivenessmentioning
confidence: 99%
“…No entanto, pesquisas evidenciam grande variabilidade nos períodos para a cultura do girassol. Tal fato reforça a ideia que há necessidade de repetir esses trabalhos em diversas condições, para que se garanta base de dados confiáveis sobre os efeitos da interferência de plantas daninhas (Brighenti et al, 2004;Knezevic et al, 2002;Silva et al, 2012).…”
Section: Introductionunclassified